Ion kinetics in an ECR plasma source - Gutiérrez-Tapia, C. (Вопросы атомной науки и техники, 2002)
In plasma reactors it is extremely important the study for achieving greater control of critical parameters such as the flux velocities and the energy distribution of ions. These quantities are functions of the reactor physical dimensions, magnetic field profile as well as the kinetic chemical reactions occurring in the discharge. In this work, a model previously reported in [1] is improved. In that model using the drift kinetic equation approach the axial and radial ion fluxes at processing zone of an ECR plasma source are calculated. Now, the ionization rates are calculated from the energy distribution function obtained by a regularization method and using the experimental data of the electric probe measurements. Also, a more exact calculation of the external magnetic field is included.